Exilul „concentraţionar” şi poezia ca libertate - Sorin Ivan (Revista de Istorie și Teorie Literară)
In Ion Caraion’s poetry, exile is, more than a poetic theme, a reality of the human being, an ontological state. This existential condition appears in a number of essential hypostases in his poetic universe: the concentrationary exile, the political exile, the geographical exile, the moral exile, the linguistic exile, the aesthetic exile, and the last exile, the Non-being. In such a context, we can talk about the exile poetry and the poetry exile in Caraion’s work, in a world as a vast prison, in an absurd universe, subject to death, in which man lives the condition of an exiled and of a victim, in which even words agonise. Ion Caraion is the exiled poet of Romanian literature. A form of exile is the concentrationary exile, in an era of terror, during the installation of the communist regime in Romania. Caraion writes a poetry of resistance, a political poetry, of extraordinary virulence, which accuses the communist regime and its dehumanizing ideology of crimes against human being and humanity. This gulag poetry is an act of dignity of the free spirit, a manifestation of freedom. It is a conversion of the aesthetic act in an essential ontological exercise, in a form of survival. The political anticommunist dimension is a coordinate of Caraion’s poetry, which should be considered in the discussions about resistance and dignity against the communist totalitarianism and dictatorship. Caraion’s poetry, in this aspect, is an affirmation of freedom and human dignity.